LIGHTNING PROTECTION SYSTEM FOR THE MAIN POWER HOUSE BUILDING SULTAN HASANUDDIN AIRPORT DEVELOPMENT PROJECT - Pratama, Dimas Yudha Ari; Purwito, Purwito; Salim, Agus (Jurnal Teknologi Elekterika, 2025)
Lightning, often called lightning, is a natural phenomenon that is common during the rainy season. Lightning appears as a flash of bright light followed by a rumbling sound called thunder. This phenomenon occurs due to the potential difference between clouds and the earth or between clouds, with negative charges in clouds being released towards the earth to achieve equilibrium. This process creates lightning and lightning sounds. This phenomenon is more common in the rainy season because of the high moisture content in the air which lowers the insulation power, making it easier for electric current to flow. The danger of lightning can cause damage to buildings, and power grids, and fatalities. This research was conducted at PT Wijaya Karya (Persero) Tbk., at the Sultan Hasanuddin Airport Development Project, Maros Regency, South Sulawesi. The research procedure begins by asking permission from the company's management, followed by data collection from the Production, Engineering, and QC teams. Data collection is carried out through literature studies, field observations, interviews with related teams, and documentation. The data obtained will be analyzed to determine the lightning protection system and earth resistance measurement at the Main Power House Building. The calculation includes the density of the lightning strike, the area of the protection area, and the frequency of the strike. The determination of the need for a protection system is carried out based on the results of the calculation, and if necessary, the protection efficiency will be calculated using the rolling ball method. From the calculation results, the minimum protection value in the rolling ball method is 9.7 meters with a maximum protection of 20 meters. In the results of the measurement of the grounding resistance for lightning rods, the following results were obtained (1.42 Ohms; 0.92 Ohms; 0.15 Ohms; 1.61 Ohms). The result does not exceed the limit of 5 Ohms.